Visible ns‐pulse laser oscillation in Pr‐doped double‐clad structured waterproof fluoride glass fibre with SESAM. Issue 7 (28th July 2017) - Kajikawa, Shota; Yoshida, Minoru; Motokoshi, Shinji; Ishii, Osamu; Yamazaki, Masaaki; Fujimoto, Yasushi
Abstract : A visible Q‐switched pulse train at 639 nm was successfully generated in a Pr‐doped double‐clad structured waterproof fluoride glass fibre with a semiconductor saturable absorber mirror. The slope efficiency was calculated as 36.3%. The pulse duration and the radio frequency were measured as 270 ns and 107 kHz at 596 mW of absorbed power, respectively. The pulse energy and the pulse peak power were calculated as 1.32 μJ and 4.87 W, respectively.